Is Kidney Transplantation From a COVID-19–Positive Deceased Donor Safe for the Recipient? - Perlin, D.V. (Transplant Proc, 2021)
INTRODUCTION: In recent months, the number of kidney transplants from deceased donors has declined significantly. One of the reasons is the possibility of infection of the recipient with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Determining the risk of transmission of coronavirus disease 2019 (COVID-19) with a donor organ is very important for developing a kidney transplantation policy during a pandemic. MATERIALS AND METHOD: We present cases of kidney transplantation from COVID-19–positive deceased donors to 2 dialysis patients 49 and 45 years old. One of them was on hemodialysis for 28 months; the other received continuous ambulatory peritoneal dialysis (CAPD). Both patients received only basic immunosuppression, including tacrolimus, methylprednisolone, and mycophenolic acid. No antilymphocyte agents were used for induction therapy. RESULTS: Cold ischemia time was 22 and 21 hours, respectively. One recipient had delayed graft function with increasing of urine output on day 8; another had immediate function. Both patients had no febrile and no other symptoms of acute respiratory disease during their hospital stay. No abnormalities on the chest x-ray were seen. No serum anti-SARS-CoV-2 IgM and IgG were detected before and during 6 weeks after surgery. Repeated nasopharyngeal swabs real-time reverse transcription polymerase chain reaction (rRT-PCR) were negative during the period. Both recipients were discharged 5 weeks after surgery with serum creatinine levels of 122 and 91 mcmol/L, respectively. CONCLUSION: Today we have no evidence of the possibility of transmission of COVID-19 from a SARS-CoV-2 positive donor to a kidney recipient. We also have no reason to suspect kidney damage by COVID-19 in a deceased donor at normal serum creatinine level.